Reproducibility of Portable OCT and Comparison with Conventional OCT - Nakamura, Marie; Hirano, Takao; Chiku, Yoshiaki; Takahashi, Yoshiaki; Miyasaka, Hideki; Kakihara, Shinji; Hoshiyama, Ken; Murata, Toshinori (Diagnostics (Basel), 2024)
Optical coherence tomography (OCT) is an indispensable instrument in ophthalmology; however, some facilities lack permanent OCT devices. ACT100, a portable SD-OCT system, allows for medical examinations at hospitals that do not have OCT and house calls. We investigated the usefulness of ACT100 by examining the reproducibility of retinal thickness measurements in 35 healthy participants with normal eyes using ACT100 and Cirrus. Using two OCTs, the OCT imaging of both eyes of each subject was performed. Macular retinal thickness was evaluated using the average value in nine lesions of the Early Treatment Diabetic Retinopathy Study (ETDRS) circle. Both models captured images in all cases. In the right eye, mean retinal thickness was significantly lower than in the ACT100 group in all regions; however, the measured values correlated well. The intraclass correlation coefficients showed the same high reliability as the Cirrus. The coefficients of variation (CVs) of both models showed little variation and high stability; however, the CV of ACT100 was significantly higher. The left eye was almost identical. Macular retinal thickness measured using ACT100 showed slightly greater variability than that by Cirrus; the reproducibility was good and correlated well with that of Cirrus. This technique is a suitable alternative to conventional OCT.